The Value of the Book „Conflict outlines: educational reality context” by V. Targamadzė - Čiuladienė, Gražina; Aramavičiūtė, Vanda (Acta Paedagogica Vilnensia, 2007)
A review of a Book „Conflict Outlines: Educational Reality Context” by Vilija Targamadzė
Keywords: educational science; monograph; V.Targamadzė